The multi-outburst activity of the magnetar in Westerlund I. Issue 3 (16th January 2019) - Borghese, A; Rea, N; Turolla, R; Pons, J A; Esposito, P; Coti Zelati, F; Savchenko, V; Bozzo, E; Perna, R; Zane, S; Mereghetti, S; Campana, S; et al.
ABSTRACT: After two major outbursts in 2006 and 2011, on 2017 May 16 the magnetar CXOU J164710.2−455216, hosted within the massive star cluster Westerlund I, emitted a short (∼20 ms) burst, which marked the onset of a new active phase. We started a long-term monitoring campaign with Swift (45 observations), Chandra (five observations), and NuSTAR (four observations) from the activation until 2018 April. During the campaign, Swift Burst Alert Telescope (BAT) registered the occurrence of multiple bursts, accompanied by two other enhancements of the X-ray persistent flux. The long time span covered by our observations allowed us to study the spectral and the timing evolution of the source. After ∼11 months since the 2017 May outburst onset, the observed flux was ∼15 times higher than its historical minimum level and a factor of ∼3 higher than the level reached after the 2006 outburst. This suggests that the crust has not fully relaxed to the quiescent level, or that the source quiescent level has changed following the multiple outburst activities in the past 10 yr or so. This is another case of multiple outbursts from the same source on a yearly time-scale, a somehow recently discovered behaviour in magnetars.